Textbook of evolutionary psychiatry : the origins of psychopathology - Brune, Martin (Oxford University Press, 2008)
This book presents a new integrative approach to understanding psychopathological conditions, embracing cognition, emotion, behaviour, and their nature-nurture interactions. Central to this approach is the introduction of human evolution into the psychiatric model, in a quest to find out why the human mind and brain evolved in the way it did.